2003
DOI: 10.1074/jbc.m304620200
|View full text |Cite
|
Sign up to set email alerts
|

A Corresponding Tyrosine Residue in the C2/Factor B Type A Domain Is a Hot Spot in the Decay Acceleration of the Complement C3 Convertases

Abstract: The cleavage of C3 by the C3 convertases (C3bBb and C4b2a) determines whether complement activation proceeds. Dissociation (decay acceleration) of these central enzymes by the regulators decay-accelerating factor (DAF), complement receptor 1 (CR1), factor H, and C4-binding protein (C4BP) controls their function. In a previous investigation, we obtained evidence implicating the ␣4/5 region of the type A domain of Bb (especially Tyr 338 ) in decay acceleration of C3bBb and proposed this site as a potential inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…DAF bound Bb via the von Willebrand factor type A (vWFA) domain rather than the serine protease domain. Functional studies with recombinant C2 and fB mutated within this domain indicated that DAF mediated its regulatory action via interactions with vWFA, and our kinetic analyses demonstrated that the Bb fragment and the vWF domain bind DAF with the same kinetic profiles and affinities (12)(13)(14). The specificity of DAF for the active convertase may be a consequence of its higher affinity for Bb compared with fB, and suggests that the regulatory function of DAF on the cell membrane is focused entirely on inhibition of activated enzymes rather than on binding to inactive proenzymes.…”
mentioning
confidence: 95%
“…DAF bound Bb via the von Willebrand factor type A (vWFA) domain rather than the serine protease domain. Functional studies with recombinant C2 and fB mutated within this domain indicated that DAF mediated its regulatory action via interactions with vWFA, and our kinetic analyses demonstrated that the Bb fragment and the vWF domain bind DAF with the same kinetic profiles and affinities (12)(13)(14). The specificity of DAF for the active convertase may be a consequence of its higher affinity for Bb compared with fB, and suggests that the regulatory function of DAF on the cell membrane is focused entirely on inhibition of activated enzymes rather than on binding to inactive proenzymes.…”
mentioning
confidence: 95%
“…The process of dissociation of the catalytic subunit Bb from the C3-convertase C3b,Bb is preceded by the binding of regulator to both the subunits of C3-convertase, C3b and Bb (40,41). We therefore asked whether the superior decay-acceleration activity of VCP against bovine C3-convertase is determined by its interaction with C3b or with Bb.…”
Section: Species Selective C3-convertase Decay Activity Of Vcp Is Primentioning
confidence: 99%
“…5), suggesting a functional role for module 1 in CP DAA. Earlier examination of CP DAA by human complement regulators suggested that dissociation of the protease subunit from the convertase is a result of binding of the regulators to C4b and C2a, followed by a conformational change in the von Willebrand factor type A (vWFA) domain (45,47,63,64). More recently, it has been suggested that dissociation of the convertases could also be a result of displacement of the protease subunit by the regulator owing to a competition posed by the regulator for the protease interaction site on the noncatalytic subunit of the convertase (51).…”
Section: Vcp Domains Critical For Daasmentioning
confidence: 99%
“…DAA involves binding of the viral complement regulator to C3b or C4b and to Bb or C2a (44,45), whereas CFA requires interaction of the viral complement regulator with C3b or C4b, followed by interaction of factor I with C3b or C4b and the complement regulator (46). To determine whether loss or gain in the CFA and DAA of the domain swap mutants was owing to difference in their binding to C3b and C4b, we measured binding of VCP and the mutants to C3b and C4b using SPR assay described earlier (41,47).…”
Section: Characterization Of Binding Of Vcp-daf and Vcp-mcp Domain Swmentioning
confidence: 99%